Pembuatan Briket Tongkol Jagung sebagai Sumber Energi Alternatif oleh Kelompok Tani Desa Titiwangi Lampung Selatan - Achmad, Feerzet; Setiawan, Darma; Hukama, Ikhwan; Lisnurani, Lisnurani; Yuniarti, Reni; Suhartono, Suhartono; Suharto, Suharto (LPPM Universitas Trunojoyo Madura, 2023)
Corn cob waste continues to increase every year. The corn cobs become waste, which is seen as having no significant economic value by the people of Titiwangi Village, so they are only used as animal feed. Efforts are being made to overcome this problem through the processing of corncob waste into briquettes. Briquettes are an alternative energy source produced from carbon-containing materials by heating them at high temperatures. The purpose of utilizing corncob waste is to reduce waste and help the economy of the people of Titiwangi Village. The implementation method used is training in making briquettes from corn cobs. The output achieved is corncob briquettes. The advantages of the resulting briquettes are that they save energy, are environmentally friendly, do not smell, do not cause new waste, and have a distinctive natural aroma.